2020
DOI: 10.1515/med-2020-0138
|View full text |Cite
|
Sign up to set email alerts
|

A review of current progress in triple-negative breast cancer therapy

Abstract: Triple-negative breast cancer (TNBC) is a particularly aggressive subtype known for its extremely high drug resistance, progression, poor prognosis, and lack of clear therapeutic targets. Researchers are aiming to advance TNBC treatment worldwide. In the past 2–3 years, more positive results have emerged in the clinical research on TNBC treatment. Based on the results, several impressive drugs have been approved to benefit patients with TNBC, including the PARP inhibitors olaparib and talazoparib for germline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 43 publications
(42 reference statements)
0
41
0
Order By: Relevance
“…These immune cells were mainly present in IS3 with the best tumor prognosis, we also observed that 47 immune checkpoint-related genes were significantly different in the two cohorts and were responsible for maintaining autoimmune tolerance and regulating the persistence and intensity of the immune response. Interestingly, the suppression of immune checkpoint genes has been confirmed to reverse the inhibition of the TIME on tumor immunity and accelerate the apoptosis of tumor cells, which is a potential new possibility for future treatment of TNBC ( Shen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These immune cells were mainly present in IS3 with the best tumor prognosis, we also observed that 47 immune checkpoint-related genes were significantly different in the two cohorts and were responsible for maintaining autoimmune tolerance and regulating the persistence and intensity of the immune response. Interestingly, the suppression of immune checkpoint genes has been confirmed to reverse the inhibition of the TIME on tumor immunity and accelerate the apoptosis of tumor cells, which is a potential new possibility for future treatment of TNBC ( Shen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the expression of estrogen receptors (ER), progesterone receptors (PGR), and human epidermal growth factor receptor 2 (HER2), three subtypes are commonly used for breast cancer clinical classification: the ER/PGR-positive subtype, the HER2-positive subtype, and TNBC, with the most aggressive behavior. TNBC accounts for nearly 15% of BC patients annually, and it is characterized by a high metastasis/recurrence rate and a short survival time ( Shen et al, 2020 ). Approximately 50% of TNBC patients who undergo radical surgery without metastasis will develop a disease recurrence ( Liedtke et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Triple-negative breast cancer (TNBC) is characterized by the absence of estrogen receptors (ER), progesterone receptors (PR), and human epidermal growth factor receptor 2 (HER2) and is highly metastatic and lethal [1,2]. Although substantial efforts have gone into identifying treatments for TNBC in recent decades, the median survival time of TNBC patients is still less than 15 months largely due to the absence of effective drugs in the clinic [3,4]. Since its discovery, TNBC has been a challenge in the cancer treatment eld [3][4][5], warranting the discovery of novel, potent therapeutics against TNBC.…”
Section: Introductionmentioning
confidence: 99%
“…Although substantial efforts have gone into identifying treatments for TNBC in recent decades, the median survival time of TNBC patients is still less than 15 months largely due to the absence of effective drugs in the clinic [3,4]. Since its discovery, TNBC has been a challenge in the cancer treatment eld [3][4][5], warranting the discovery of novel, potent therapeutics against TNBC.…”
Section: Introductionmentioning
confidence: 99%
“…About 15% of BC cases are triple-negative breast cancers (TNBCs), lacking the expression of ERα, PR and HER2-amplification and are thus not responsive to targeted therapies against ERα or HER2. These cancers are associated with a poorer prognosis due to a higher rate of metastatic progression and resistance to treatment (16,17). Notably, TNBC may be responsive to estrogen stimulation via ERα-independent pathways, promoting tumor formation and progression via different molecular mechanisms (18).…”
Section: Introductionmentioning
confidence: 99%